What does China think? - Leonard, Mark, 1974- (PublicAffairs, 2008)
A leading foreign policy expert offers a look at the inner workings of China to explore a hidden world of intellectual debate that is fueling a new Chinese revolution and to reflect on what this will mean in terms of both China as a nation and its role in global affairs.